Assessment of bush meat exploitation by hunters in Ifon Area of Ondo state, Nigeria (2019)
This study assessed the bush meat exploitation by hunters in Ifon Area of Ondo State. Questionnaire was administered as interview guide to all 30 members of hunters association in the area as well as personal visits and observations were made, while discussions and interviews were made use of to obtain information on the study area. Data collected was analysed using descriptive statistics (Frequency count and Percentage, Measure of Central Tendency and Measure of Dispersion). Results reveal that the bush meat species commonly found and consumed, reasons for bush meat hunting, the effect of bush meat exploitation on the area and the level of awareness with regard to the negative impact of bush meat exploitation on Wildlife Conservation. Based on these findings, it is essential that, logging companies are encouraged or urged not to facilitate bush meat hunting and transportation in their concessions. Likewise, social marketing activities should be put in place to attempt to direct consumer preferences for animal protein away from bush meat species that are particularly susceptible to over-exploitation.